THE CONTRIBUTION OF FISHERMEN'S WIVES IN ENHANCING HOUSEHOLD ECONOMY IN GAMPONG PUSONG LAMA, LHOKSEUMAWE CITY - Nida Kholila; Nopri Yanto; Wahyu Isnanda Nasution (LPPM Universitas Malikussaleh - Indonesia, 2026)
This research was conducted in Gampong Pusong Lama, Banda Sakti District, Lhokseumawe City. Gampong Pusong Lama, fishing families depend on the husband who works as a capture fisherman. However, problems often arise when the fishermen go out to sea, such as bad weather, which results in low income and makes it difficult to meet the family's growing daily needs. As a result, many wives of capture fishermen also take part in working and contribute to helping their husbands increase the family's income, as is the case in Gampong Pusong Lama, Banda Sakti District, Lhokseumawe City. This study aims to examine the extent of the contribution made by the wives of capture fishermen in improving the household economy in Gampong Pusong Lama, Banda Sakti District, Lhokseumawe City. The data analysis method used is quantitative analysis. The research findings show that most wives of capture fishermen in Gampong Pusong Lama work as traders, such as kiosk owners, mobile credit sellers, small shopkeepers, fried snack vendors, grilled meatball sellers, rice vendors, vegetable stall owners, coffee shop operators, and miso soup stall owners. The average monthly income of the 40 respondents was IDR 1,348,200 or 53.79%, which is classified as a moderate contribution to the household income and is higher than the income of their husbands who work as fishermen, which amounted to IDR 1,028,000.